2010
DOI: 10.1039/c0an00005a
|View full text |Cite
|
Sign up to set email alerts
|

Application of PARAFAC to determination of distribution constants and spectra of fluorescent solutes in micellar solutions

Abstract: Steady state fluorescence excitation emission matrices (EEMs) and time-resolved fluorescence of biphenyl (BP) and 2,5-diphenyloxazole (PPO) dissolved in aqueous solutions of sodium dodecyl sulfate (SDS) were measured as a function of micelle concentration. Parallel factor analysis (PARAFAC) was applied for the first time to the determination of the distribution of solutes between the bulk aqueous phase and the SDS micellar phase, as well as their excitation and emission spectra in both phases. The raw scores o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Another issue worth noting is that determining the ''similarity'' between two components' spectra can be difficult; for example, in a recent paper we found that the spectra of solutes (biphenyl or 2,5-diphenyloxazole (PPO)) in water phase and in micelle phase of sodium dodecyl sulfate were quite similar but not identical. 17 Because of the polarity difference in the two phases, the spectra in the two phases are not strictly identical. The very similar spectra in the two phases would be falsely forced to be identical when applying PARALIND in the absence of a priori knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Another issue worth noting is that determining the ''similarity'' between two components' spectra can be difficult; for example, in a recent paper we found that the spectra of solutes (biphenyl or 2,5-diphenyloxazole (PPO)) in water phase and in micelle phase of sodium dodecyl sulfate were quite similar but not identical. 17 Because of the polarity difference in the two phases, the spectra in the two phases are not strictly identical. The very similar spectra in the two phases would be falsely forced to be identical when applying PARALIND in the absence of a priori knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Excitation light intensity incident on the uorescence cuvette as a function of lamp output wavelength, and uorescence detector sensitivity as a function of uorescence wavelength, were both corrected as recommended by the uorometer user's manual. The scattering light signals in the EEMs were eliminated from the analysis according to an approach employed previously, 7,27,28 which consisted in replacing the data region containing scattering light signals with "NaN" (not a number) using a home-written program implemented in a Matlab 6.5 soware package (Mathworks, Natick, US). The UV-Vis absorbance at wavelengths of 250 through 600 nm with 1 nm intervals was measured in 1 cm quartz cuvettes on a Shimadzu 1700 spectrophotometer in double-beam mode.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…30 This method has proven efficient in IFE correction for uorescence data in previous PARAFAC studies. 25,27,31,32 The concentrations of DOC were determined by high temperature combustion on a Shimadzu TOC-VCPH instrument with a detection limit of 0.06 mg L À1 . A non-purgeable DOC measurement mode was employed, in which the sample was acidied to pH 2 by aliquots of concentrated HCl and then purged with high purity (>99.995%) oxygen gas to remove inorganic carbon before determination of DOC concentration.…”
Section: Laboratory Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid light scattering problems, the EEMs of blank water were extracted from the data EEMs, and fluorescence intensities at emission wavelength not far different than excitation wavelength (wavelength difference less than 10 nm) were set to NaN (not‐a‐number, a variable that can be handled by Matlab) to refer to missing data. The use of missing data to replace scattering light in EEMs has been successfully implemented in previous studies 3, 16–18. Based on the formula derived by MacDonald et al .…”
Section: Methodsmentioning
confidence: 99%